Convergence in airline operations: The case of ground times. (June 2019) - Lange, Anne; Sieling, Julian; Gonzalez Parra, Garoe
Abstract: Passenger airline business models have been converging in the recent past. Our study addresses differences in ground operations. The organization of ground operations is seen as one distinguishing factor between airline business models. We investigate taxi-in, taxi-out, and turnaround times of aircraft and study the current status of the relation between airline ground times and airline business models. Our study rests on automatic dependent surveillance broadcast (ADS-B) data to investigate ground times of aircraft. We identify that there currently remains a clear differentiation of airline ground times between the business models in spite of the business model convergence in the market. Highlights: We analyze aircraft ground times based on ADS-B data. We find that differences in ground times persist among airline business models. Turnaround times even nowadays increase from LCC over HYC to FSC. Convergence in airline ground operations cannot (yet) be observed.